Z historii kałmuckich elit władzy - Bodio, Tadeusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The model of the political elite of the Kalmykia Republic has been strongly affected by the four hundred years of processes that have shaped the nation and the state. Historical archetypes constitute a significant element of Kalmykian political psychology. Their synthesis forms a kind of foundation that to a large extent sets the norms by which the power elite is elected and operates. It is also reflected in the internal divisions of this elite and the relations with the central authority of the federation. The power of this psycho-cultural foundation became apparent immediately after the collapse of the USSR, when ideas of reviving the traditional institutions of power became very popular in the republic. This paper attempts to reconstruct the most important aspects of the formation of the power elite and their operation, and to reveal their role in the processes that were decisive for the formation of the Kalmyk nation, with its own state entity in the form of a republic, under the circumstances of Russian colonization.